Toddalolactone Protects Lipopolysaccharide-Induced Sepsis and Attenuates Lipopolysaccharide-Induced Inflammatory Response by Modulating HMGB1-NF-κB Translocation - Ni, Jingyu; Zhao, Yuxuan; Su, Jing; Liu, Zhihao; Fang, Shiming; Li, Lan; Deng, Jie; Fan, Guanwei (Frontiers in Pharmacology, 2020)
Toddalolactone(TA-8) is a main compound isolated from Toddalia asiatica (L.) Lam.,and its anti-inflammatory activity and anti-inflammatory mechanism are less studied.In the present study, we investigated the anti-inflammatory effects of TA-8. Our experimental results showed that TA-8 inhibited the production of pro-inflammatory cytokines by both LPS-activated RAW 264.7 cells and septic mice. Moreover, TA-8 suppressed the NF-κB transcriptional activity, reduced the nuclear translocation and phosphorylation of NF-κB, blocked the translocation of HMGB1 from the nucleus to cytosol, and decreased LPS-induced up-regulation of TLR4 and IKBKB expression,and decreased IκBα phosphorylation.In addition,the administration of TA-8 decreased LPS-induced liver damage markers (AST and ALT),attenuated infiltration of inflammatory cells and tissue damage of lung, liver and kidney,and improved survival in septic mice.Taken together,these results suggested that toddalolactone protects LPS-induced sepsis and attenuates LPS-induced inflammatory response by modulating HMGB1-NF-κB translocation.TA-8 could potentially be a novel anti-inflammatory and immunosuppressive drug candidate in the treatment of sepsis and septic shock.